Regional Risk Sharing and Redistribution - The Role of Fiscal Mechanisms in Switzerland - Lars P. Feld; Christoph A. Schaltegger; Janine Studerus (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyses the importance of fiscal mechanisms for regional risk sharing and redistribution in Switzerland. Switzerland is a particularly interesting setting in this context because it features both a high level of fiscal autonomy for Swiss cantons and explicit fiscal transfers between the federal government and the cantons. Based on panel-data analysis we study the redistributive and stabilizing properties of fiscal equalization transfers, federal government transfers in general, direct federal taxation, the unemployment insurance scheme and the first pillar pension scheme. We find a combined redistributive effect of these mechanisms of about 20%. This means that long-run income differentials of 1 Swiss Franc between cantons translate into differences of long-run disposable income after taxes and transfers of about 80 cents. The combined contemporary stabilization effect with respect to short-term income fluctuations amounts to less than 10%, which is a small effect compared to previous findings for other countries.
Keywords: E62; H10; H70; 330; regional risk sharing; redistribution; fiscal transfers